Conscientious objection in the design of artificial intelligence: when the law questions the algorithm - Coaquira-Flores, Angel Jeancarlo (2025)
The disruptive expansion of Artificial Intelligence (AI) has had a cross-cutting impact on all areas of human activity, offering significant advantages but also substantial risks to human rights. Thus, among the problems arising from its misuse are mass surveillance, social manipulation, and the application of intelligent systems for military purposes. Thus, in response to this problem, a debate has arisen about the relevance of recognizing the right to conscientious objection in the design and development of technologies, particularly in the field of AI. Consequently, this article examines the legal nature of conscientious objection from a doctrinal and normative perspective, thus making it possible to analyze its possible configuration as an ethical defense mechanism against potentially harmful technological projects. Finally, we propose essential elements that could characterize a possible conscientious objection in the technological field, with an emphasis on AI, advocating for specific regulation that reconciles the moral integrity of professionals with the public interest.